PERAN EMOTIONAL FREEDOM TEHNIQUE (EFT) DALAM MENGATASI KECEMASAN ORANG TUA DALAM PEMBELAJARAN BERBASIS ONLINE - Jumrotun Ni'mah; Uswatun Insani; Evi Supriatun (Jurnal Pengabdian kepada Masyarakat (NADIMAS), 2022)
Online learning is learning without face to face directly between teachers and students. With online learning often makes parents anxious. Anxiety is a state of restlessness, uncertainty, or fear that is a manifestation of an individual's psychological or physiological response to an unpleasant or threatening situation. This community service aims to increase the knowledge of teachers and parents about how to overcome anxiety with Emotional Freedom Technique (EFT) therapy. EFT is an emotional healing technique that can also heal the symptoms of physical illness.” The working principle of EFT is to harmonize and repair the disturbed energy system in the body, through stimulation of the body's energy points called meridians by tapping (light tapping). Parents of students stated that there was a decrease in anxiety after being given EFT by expressing gratitude and sincerely accepting the circumstances experienced, especially online learning which requires extra assistance from parents to help students achieve learning competency targets.